Integrated Science E-Module assisted by the Flip PDF Professional Application to Integrate Character Education Values in Science Learning for Junior High Schools - Prima Aswirna; Media Roza; Mela Zainia (Journal of Natural Science and Integration, 2023)
The current impact of globalization has made Indonesian people forget about character education. The National Education System declared that national education has the function of developing abilities and forming dignified national character and civilization in the framework of educating the nation. In this regard, rapid technological changes have brought the popularity of computer-based learning as an effort to develop specific knowledge and skills in the educational environment. In order to establish the cited functions, education provides teaching materials that can be accessed independently by students. This study aims to develop an Integrated Science E-Module to integrate the values of character education at Junior High Schools. In this study, the Integrated Science E-Module prototype was designed using the Plomp model. Moreover, a validated functional prototype was also carried out. Based on results of the analysis, the data demonstrated that the Integrated Science E-Module is successful in integrating the values of character education in student learning and the results of the product developed have assisted them to have character values such as religious, responsible, curious, have mutual cooperation, communicative, and care for the environment.Keywords: integrated science e-module, flip pdf professional, values of character education